THE INFLUENCE OF SOCIAL SUPPORT AND ACADEMIC SELF-EFFICACY ON ACADEMIC ADJUSTMENT OF CLASS X BUSINESS MANAGEMENT STUDENT AT SMKN 48 JAKARTA - Siti Nikmaturofiqoh; Yohana, Corry; Fidhyallah, Nadya Fadillah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The purpose of this study was to see how social support and academic self-efficacy influence the academic adjustment of students in class X Business Management (SMKN 48 Jakarta). The research method used is a survey method with a quantitative approach. Students from class X Business Management SMKN 48 Jakarta served as the population in this study, with a sample size of 120 students. The data analysis technique used was multiple linear regression analysis using the IBM SPSS version 25 application. The first test performed was the validity and reliability test of the instrument, with the results of the validity test of p-value 0.000 <0.05 and the results of the reliability test being a Cronbach's alpha value of 0.902 . The second test is the classic assumption test; all the data in this study pass the classic assumption test. The next test, namely multiple linear regression analysis, obtained the equation Y = 14.456 + 0.226 X1 + 0.237 X2. The next test, namely the hypothesis test with the t test, obtained a significance value of 0.000 <0.05 and the f test had a significance value of 0.000 <0.05. The result of this research is that all hypotheses can be accepted.